Induced dedifferentiation of barley (Hordeum vulgare L.) embryonic cells and its relationship with agronomic traits - Naseri, R.; Cheghamirza, K.; Zarei, L.; Saroei, E. (Cellular and Molecular Biology, 2017)
This study was carried out to investigate the response of 42 Iranian and European barley (Hordeum vulgare L.) cultivars to induced dedifferentiation of embryonic cells via immature embryo culture and understand the relationship between embryo culture characters and agronomic traits. The cultivars were evaluated for dedifferentiation of embryonic cells or callus induction from immature embryo culture based on a completely randomized design with unequal replication. Immature embryos were placed scutellum down on cell dedifferentiation medium based on MS and supplemented with 2.5 mg/l 2,4-D. The developed calli were transferred to MS regeneration medium with different concentrations and combinations of plant growth regulators. The results of group comparisons showed that Iranian cultivars were greater than European cultivars regarding callus growth rate, callus primary diameter and total regenerated plantlets. The path correlation analysis revealed that grain width and kernel filling period had the highest positive and negative direct effects on embryo culture traits, respectively. Clustering cultivars based on the embryo culture characters and agronomic traits divided the cultivars into three groups. The third group consisted of the cultivars which all of them were with the highest mean for flag leaf length, days to anthesis, grain yield, callus growth rate and callus primary diameter. Mantel test revealed a negative (-0.101) and significant correlation (P<0.01) between embryo culture characters and agronomic traits. The significant relationships between few numbers of embryo culture characters and agronomic traits confirm that these characteristics could be genetically dependent and also tissue culture characters can be estimated from agronomic data.